1998
DOI: 10.1161/01.cir.98.25.2899
|View full text |Cite
|
Sign up to set email alerts
|

Offspring of Normal and Diabetic Rats Fed Saturated Fat in Pregnancy Demonstrate Vascular Dysfunction

Abstract: A high-fat diet in pregnancy led to vascular dysfunction in rat weanlings and young adult offspring. Vascular function further deteriorated in weanlings if the maternal rat was diabetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
64
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 24 publications
17
64
0
Order By: Relevance
“…Thus, vascular reactivity was expected to change in the presence of high levels of LDL cholesterol, especially in the female offspring. Increased vascular contractility and decreased vasodilator capacity has been observed in adult models of maternal overnutrition and CVD (25,37,38). Feeding a high-SFA maternal diet caused a reduction in vascular contractility, whereas vasodilator capacity was unaffected in our study.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Thus, vascular reactivity was expected to change in the presence of high levels of LDL cholesterol, especially in the female offspring. Increased vascular contractility and decreased vasodilator capacity has been observed in adult models of maternal overnutrition and CVD (25,37,38). Feeding a high-SFA maternal diet caused a reduction in vascular contractility, whereas vasodilator capacity was unaffected in our study.…”
Section: Discussionsupporting
confidence: 50%
“…L-NAME caused a small increment in the contractile responses to KCl and PE in S/C males, which would be consistent with our hypothesis. Previous studies dealing with maternal overnutrition during pregnancy have indicated an impairment of AChinduced vasorelaxation, albeit using smaller-caliber resistancetype arteries, where the endothelial-derived relaxing factors differ from those present in aorta, e.g., endothelium-derived hyperpolarizing factor (26,35,36,38). Female offspring did not show any alterations in the relaxation responses to ACh and SNP.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A loss of AA and DHA would reduce liquidity and the liberal mechanical properties normal to active cell membranes. Such a defect in the endothelial membrane could create susceptibility to vascular dysfunction as experimentally demonstrated in rats [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have provided evidence that individual fatty acids have distinct roles in development. The n-3 LCPUFA are recognised as essential fatty acids for fetal and infant development, particularly the development of the brain and central nervous system [9], while perinatal exposure to excess levels of saturated or trans fats during has been linked to an increased risk of obesity, insulin resistance and cardiovascular deficits [10,11]. Consequently, it is important to understand the impact of maternal diet on the balance of specific fatty acids in the milk.…”
Section: Introductionmentioning
confidence: 99%